The assessment of biofuel potential as a local renewable energy source - Zelianukha, Аlena; Rodzkin, Aleh; Glukhovskij, Viktor (Journal of the Belarusian State University. Ecology, 2024)
Local energy sources are solid fossil fuels, which play a role in the energy balance of the Republic of Belarus. The category includes both renewable energy sources and non-renewable, primarily peat. The most promising sources of vegetable biofuels for energy purposes in the Republic of Belarus are natural stocks after grain crops (straw), corn for grain, flax processing and natural wetlands grasses which not used as feed for agricultural livestock. The total potential for obtaining biomass production for energy purposes in the country, according to expert estimates, is over 2 million toe, of which at present, according to calculations based on a large number of bioenergy installations, no more than 10% are used. A credible and major profit of renewable biomass using is zero greenhouse gas emissions. The amount of carbon dioxide that is released into the environment is utilized by plants through the process of photosynthesis. The potential reduction in greenhouse gas emissions in the event of replacing fossil fuels in the region with biofuels on a national scale totals more than 4 million tons of CO2 - equivalent. When evaluating the environment of biomass, it must be taken into account that utilization of biomass for renewable energy is also an environmental impact factor. This influence is characterized by chemical pollution of the biosphere (emissions and discharges of pollutants in gaseous, liquid and solid states), thermal pollution of the air and water bodies, physical impact, as well as the withdrawal of natural resources for technological needs and the placement of the main site of an energy facility. According to the results of experimental studies of solid local fuels, it was found that renewable biofuel is more environmentally friendly to compare with briquettes from peat, since the contents of heavy metals, nitrogen and sulfur in straw and wood waste samples is significantly less than in peat.
Keywords: biofuel; straw; peat; renewable energy sources; environmental impact; heavy metals